Factors Associated with Decision Making in Treatment of Health Problems among Elderly People in Dhital, Kaski District - Dhungana, Prabati (Prithvi Academic Journal, 2020)
Self-determination of one’s own treatment process is one of the major decision makings of an individual’s life. It is even more crucial among elderly population as old age brings multiple physical and mental challenges to overall well-being of an individual. This paper aims to find the factors associated with decision making in treatment of health problems of the elderly people. The study was conducted in Dhital Village of Kaski District. Out of 198 elderly people with aged 60 years and above, 131 respondents (at 5% margin of error and 5% level of significance) were randomly selected using simple random sampling techniques. The information was collected by using semi-structured questionnaires through interview techniques. Chi-squared test was used to find the factors associated with the decision making in treatment. The decisions of more than two-third (69.5%) of the respondents were taken by their family members whereas almost one-third (30.5%) of the decisions were self-made. The proportion of the females who made their decision for treatment themselves is less than that of males. The results of the study showed that gender, literacy level, family type, money expensed for treatment, and walking distance to health centers were the major factors associated with decision making in treatment of health problems. It is believed that the findings of this study can help facilitate the better use of health facilities and add a significant contribution in the formulation of aging-friendly policies.